Antioxidant Activities of Natural Compounds from Caribbean Plants to Enhance Diabetic Wound Healing - Laura Accipe; Alisson Abadie; Remi Neviere; Sylvie Bercion (MDPI AG, 2023)
Diabetic wound healing is a global medical challenge. Several studies showed that delayed healing in diabetic patients is multifactorial. Nevertheless, there is evidence that excessive production of ROS and impaired ROS detoxification in diabetes are the main cause of chronic wounds. Indeed, increased ROS promotes the expression and activity of metalloproteinase, resulting in a high proteolytic state in the wound with significant destruction of the extracellular matrix, which leads to a stop in the repair process. In addition, ROS accumulation increases NLRP3 inflammasome activation and macrophage hyperpolarization in the M1 pro-inflammatory phenotype. Oxidative stress increases the activation of NETosis. This leads to an elevated pro-inflammatory state in the wound and prevents the resolution of inflammation, an essential step for wound healing. The use of medicinal plants and natural compounds can improve diabetic wound healing by directly targeting oxidative stress and the transcription factor Nrf2 involved in the antioxidant response or the mechanisms impacted by the elevation of ROS such as NLRP3 inflammasome, the polarization of macrophages, and expression or activation of metalloproteinases. This study of the diabetic pro-healing activity of nine plants found in the Caribbean highlights, more particularly, the role of five polyphenolic compounds. At the end of this review, research perspectives are presented.